How do you differentiate f(x)=(2x-3)^3 using the chain rule? Calculus Basic Differentiation Rules Chain Rule 1 Answer Sonnhard May 27, 2018 f'(x)=6(2x-3)^2 Explanation: By the Chaine rule we get f'(x)=3(2x-3)^2*2 Answer link Related questions What is the Chain Rule for derivatives? How do you find the derivative of y= 6cos(x^2) ? How do you find the derivative of y=6 cos(x^3+3) ? How do you find the derivative of y=e^(x^2) ? How do you find the derivative of y=ln(sin(x)) ? How do you find the derivative of y=ln(e^x+3) ? How do you find the derivative of y=tan(5x) ? How do you find the derivative of y= (4x-x^2)^10 ? How do you find the derivative of y= (x^2+3x+5)^(1/4) ? How do you find the derivative of y= ((1+x)/(1-x))^3 ? See all questions in Chain Rule Impact of this question 8465 views around the world You can reuse this answer Creative Commons License